Implementasi Pembelajaran Bahasa Arab dengan Buku Ajar Al-Muyassar fi Fahm Qowaid Al-Arabiyah bi Al-Thawila di SMP Takhassus Al-Qur’an Kalibeber - Shabrina Khalina; Robingun Suyud El Syam; Ahmad Zuhdi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This thesis aims to find out the implementation of Arabic language learning with the textbook "Al Muyassar Fi Fahm Qawaid Al Arabiyah Bi Al Thawila" at Takhassus Al Qur'an Junior High School. This thesis uses a qualitative approach, where the type of research is descriptive in the field. Data collection techniques use observation, interviews and documentation. The analysis techniques used are data reduction, data presentation and conclusion drawn. The results of the study show that learning Arabic using the Al-Muyassar fi Fahm Qowaid Al-Arabiyyah bi Al-Thowila textbook is effective in improving understanding of Arabic grammar, especially in the discussion of qowaid. Systematic learning structures, table-based approaches, and step-by-step exercises help students understand language patterns more clearly. The lecture, question and answer, drill, and group discussion methods enrich the learning process, making it more interactive. Periodic evaluations ensure students' understanding before moving on to the next material. Overall, this combination of textbooks and teaching methods has been shown to significantly improve students' Arabic language skills. The teacher appreciated the systematic and gradual presentation of the material, as well as the use of tables that helped in understanding nahwu and shorof. The Arabic language learning is supported by a systematic book structure, teacher competence, a conducive learning environment, and active student involvement. These factors help students understand nahwu and shorof better. However, some obstacles are still faced, such as limited vocabulary, limited learning time, and differences in students' ability to understand the material. Therefore, more varied teaching strategies and additional support are needed to optimize learning outcomes.